A Correlation between Environmental Knowledge and High School Student Coral Reefs Concervation’s Concern at Kepulauan Seribu - Sayogo, Budiarto Heru; Seribulan, M. N. Matondang; Istiadi, Yossa (Biosfer: Jurnal Pendidikan Biologi, 2015)
Knowledge is an important factor in appearing care. As well as knowledge of high school student around Pulau Pramuka in order to bring conservation principle in the area. The aim of this research was to find out the correlation between environmental knowledge and coral reefs conservation concern. This research was held on February 2015 at SMAN 69 Jakarta. The research method used was descriptive with survey technique bycorrelational study. The sample reserach was 43 high school students grade X. The regression model was . Coefficient correlation was 0,395 that means there was low correlation between environmental knowledge of high school student and their care about coral reefs conservation. Environmental knowledge about coral reefs conservation gave contribution of 15,60% on high school student care about coral reefs conservation. The research result concluded that there was correlation between environmental knowledge and coral reefs conservation concern.